Strategi Pengembangan Ekonomi Lokal Untuk Meningkatkan Daya Saing Pada Industri Batik Di Kabupaten Tulungagung Jawa Timur - Mohamad Salman Huda (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
Batik industry is an industry sector that become a mainstay for local and export markets, especially post – textile sector . This study aims to analyze local economic development strategies to improve competitiveness in batik industry in Tulungagung regency. The research problem is proposed to find out the problem of the solution on solution of local economic development and batik industry competitiveness in Tulungagung Regency . This research is a qualitative research and the method used is survey method and analysis used by SWOTanalysis. Result of research analysis concluded; A) Determining market segmentation to be addressed, based on demographic , geographical and buyer behavior variables , B) Determining target market to be addressed those inside and outside Tulungagung including overseas, C) Improve human resource development (HR) program in quality and design, due to the fact that consumers are very fond of the characteristics of certain goods, such as: good quality with unique colors, design and motifs.D) Continuously conduct market research and development to facilitate product innovation efforts , so that the products sold are not behind competitors, E) Implement pricing policies that compete with competitor prices , F) Increase appreciation , implementation ,and protection of tipycal batik motif area trough intellectual property rights , G) Promotion of promotional program aimed at introducing product innovation and promoting sales , such as : exhibition participation at home and abroad , opening marketing outlets in strategic location of export , H) Fostering good relationships with customers and distributors so as to expand distribution troughout the country.